SPEAKING ANXIETY IN FOREIGN LANGUAGE LEARNING: A QUALITATIVE STUDY OF UNIVERSITY STUDENTS IN KAZAKHSTAN (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
Foreign language speaking anxiety is widely recognized as a major factor that negatively affects learners’ oral performance and participation in language classrooms. Despite extensive international research on this topic, limited attention has been given to speaking anxiety in the context of foreign language learning in Kazakhstan. The present study aims to explore the nature of speaking anxiety and to identify the factors that contribute to and reduce anxiety among foreign language learners. Adopting a qualitative research design, the study involved students from a university department of foreign languages studying Chinese, English, German, and Turkish. Data were collected through the Foreign Language Classroom Anxiety Scale (FLCAS) and semi-structured phenomenological interviews consisting of ten open-ended questions. The interview data were transcribed verbatim and analyzed thematically. The findings indicate that most students perceive speaking anxiety as a significant barrier to effective language learning, particularly during oral activities. Key anxiety-inducing factors include fear of making mistakes, negative evaluation by peers, public correction by teachers, low self-confidence, and limited language proficiency. Conversely, supportive teacher attitudes, constructive feedback, peer collaboration, and increased speaking practice were identified as important anxiety-reducing factors. Students reported physical, emotional, and behavioral manifestations of anxiety, such as nervousness, embarrassment, and avoidance of speaking tasks. Differences in anxiety levels were also observed across languages, with Chinese reported as the most anxiety-provoking and English as the least. The study underscores the importance of creating a supportive and low-anxiety classroom environment to enhance students’ speaking confidence and communicative competence.